Powwow day - Sorell, Traci (Charlesbridge, 2022)
Because she has been very ill and weak, River cannot join in the dancing at this year's tribal powwow, she can only watch from the sidelines as her sisters and cousins dance the celebration--but as the drum beats she finds the faith to believe that she will recover and dance again.